The localization of torts pursuant to Art. 4 of the Rome II Regulation between “lex loci damni directi”, common habitual residence and escape clause - Sartori, Federica (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The Italian Supreme Court has clarified the interpretation of Art. 4 (1) of Rome II, reaffirming that in road traffic accidents, the applicable law is that of the place where the primary victim sustained physical injuries, as the lex damni coincides with the lex loci actus identifying a peculiar lex loci damni directi. However, if both the direct victim and the person claimed to be liable share a common habitual residence, the law of that residence applies as an exception. Since the European Commission’s Report on Rome II did not raise significant issues or propose reforms about Art. 4, it is preferable for case law to remain consistent, ensuring the principles of Rome II are applied as an “acte claire”.